Assistência farmacêutica no contexto da atenção primária à saúde de um município brasileiro - Guimarães, Sandra da Silva (2020)
In the National Medicines Policy (PNM), the reorientation of Pharmaceutical Assistance (PA) is one of the guidelines in which it establishes that its model is organized in such a way that it is not restricted to the acquisition and distribution of medicines. The actions included in this field of assistance, within the scope of the three spheres of the Unified Health System (SUS), must encompass all activities related to the promotion of access and the rational use of medicines. In PHC as a gateway to health services, there is a need for periodic assessments and monitoring to improve care for the assisted population and the implementation of new services. The objective of this study was to evaluate Pharmaceutical Assistance, in the context of Primary Health Care (PHC) in a municipality in the northeast of Brazil, considering the indicators of access, quality and Rational Use of Medicines (URM), recommended by the World Health Organization. Health. The methodology used was the application of the set of indicators proposed by WHO in the dimensions of access, quality and rational use of medicines. 28 (twentyeight) Basic Health Units (UBS) were visited and 150 (one hundred and fifty) user interviews were carried out. The results found were an average of 67.6% of the availability of medicines in pharmacies in basic health units and a value of 93.3% for the Central de Abastecimento Farmacêutico, a percentage of 78.8% of medicines dispensed from the total of prescription drugs, a geographical accessibility to the dispensing unit of 99.3% and for the proper conditions of conservation, of the drugs in pharmacies, an average value of 78.6% was found, it was not possible to obtain data for the calculation the average time of shortages in pharmacies / medicine dispensaries in health units due to the lack of records in these places. The results for indicators related to rational use were an average of 2.2 drugs per prescription; 22.6% of prescriptions with antibiotics; 3.7% of prescriptions with injectables; 93.3% of prescription drugs listed in RENAME; 90.8% prescribed by generic name, absence of pharmacists, fractionation of primary packaging and 28.6% of the availability of essential drug lists. Some indicators were consistent with the values recommended by the WHO, but it is observed that there is a need for training, institution of changes in the service to improve comprehensive health care, including all the tools necessary for the rational use of medicines.